Fibrinolysis and the Immune Response in Trauma - Medcalf, Robert L.; Keragala, Charithani B.; Draxler, Dominik F. (Seminars in Thrombosis and Hemostasis, 2020)
It has long been known that the fibrinolytic system becomes activated following trauma. At first glance, this is not at all surprising and would appear to be in response to coagulation and the apparent need to remove blood clots and restore blood flow. However, in a bleeding patient, the opposite is what is actually needed. Therefore, one may ask why the fibrinolytic system gets activated in the first place or is there another purpose? Or is it that the waxing and waning of hemostasis in such severely injured patients creates a “moving target” such that the fibrinolytic system itself is constantly responding to changing circumstances? Depending on the injury modalities and the time point post injury, the fibrinolytic system could be either turned on or off. Various theories now abound that offer new insights into the turmoil and paradoxes associated with the fibrinolytic system in this unique setting and the use of antifibrinolytic agents. While this presents one conundrum, there is also another dimension to add to this discussion that has nothing to do with hemostasis per se but rather with the modulation of other critical processes that are also essential for optimal recovery following severe injury. Indeed, overwhelming data are now supporting an important role of the fibrinolytic system in the removal of necrotic tissue (mortolysis) and as a modulator of the innate immune response. Therefore, what is really going on when the fibrinolytic system decides to go into overdrive and generate plasmin, albeit even briefly after a traumatic event? Moreover, what other consequence may occur when antifibrinolytic agents are administered? This review will address this developing story and will outline a hypothesis that places the fibrinolytic system as a gateway to a myriad of processes that are not only linked to fibrin removal but are also broader players in the modulation of innate immunity.
Keywords: fibrinolysis; immune response; trauma; inflammation; antifibrinolytic agents